A BRONZE BROOCH CASTING MOULD IN EASTERN BOHEMIA FROM THE PERIOD OF THE MARCOMANNIC WARS - Vich, David; Kmošek, Jiří (Romisch-germanisches zentralmuseum, 2020)
A half of a mould made from an alloy of copper, tin, zinc and a considerable percentage of lead intended for the production of brooches of Type Almgren 132 was discovered at a Germanic settlement in the cadastral area of Koci, Eastern Bohemia, dated by other finds to the period of the Marcomannic Wars. Finds of production waste indicate that non-ferrous metals were worked there some time around the Marcomannic Wars. Brooches of Type Almgren 132 have been very rarely documented from the territory of Bohemia and Moravia. J. Tejral points out the specific situation in the Central Danube region after Commodus had made peace with the Germans, as we encounter an intensive inflow of Roman imports into the East Germanic milieu while products of East Germanic origin also appear there. J. Tejral explains this situation in the rise of specific conditions for mutual cultural exchange, in which the hinterland of Noricum and Pannonia held an extraordinary position. The territorial impact of these manifestations was probably much greater than it has seemed so far, however.
Nález bronzového kadlubu na odlévání spon z východních Čech
Keywords: Bohemia; migration period; casting mould; brooches Type Almgren 132; ED-XRF; Čechy; období stěhování národů; licí forma; spony typu Almgren 132; ER-XRF